Validity of the Environmental Change and Environmental Conservation Booklet Integrated with Local Wisdom - Fitri Arsih; Tri Putri Wahyuni (Science Journal Get Press, 2024)
This research aims to develop and validate a biology learning booklet that integrates local wisdom on the topics of Environmental Change and Environmental Conservation for 10th-grade high school students in Phase E. The research method used is descriptive qualitative with validation through Focus Group Discussion (FGD). The booklet was developed by integrating local wisdom values and environmental issues in Padang City. Validation was conducted on three main components: material, construction, and language. The validation results show that the booklet has an average validity score of 3.3, which falls into the valid category. This booklet is designed to develop students' problem-solving skills through integrated learning questions and activities. The study concludes that the developed booklet is valid and has the potential to enhance the effectiveness of contextual and meaningful biology learning by integrating local wisdom. It is recommended to conduct further research on the practicality and effectiveness of the booklet in classroom learning implementation.